Sustainability of pharmaceutical expenditures in the German social health care system - Thomas Hammerschmidt (Technische Hochschule Rosenheim, 2022)
Background: Pharmaceutical expenditure grow strongly in most health care systems. Especially high prices of new drugs are perceived to be driver of growth which might threaten the sustainability of financing drugs. Objective: The study aims to analyse a) whether German health policies can achieve sustainable growth of pharmaceutical expenditure, and b) which therapeutic groups fasten and slow pharmaceutical growth based on price and/or volume effects. Methods: Annual growth rates of pharmaceutical expenditure in the German social health insurance (SHI) between 2006 and 2018 are compared with indicators reflecting the ability to pay. Annual growth rate in therapeutic subgroups are analysed with respects to volume and price developments. Results: Without policies to control pharmaceutical spending, annual growth rates are significantly higher than the growths of indicators of ability to pay. After accounting for the savings from health policy measures, net pharmaceutical expenditure does not grow significantly faster than ability to pay. Policies mainly targeting generic drugs achieve threefold savings compared with policies targeting at patent-protected drugs, although the latter account for more than halve of the expenditure. A limited number of therapeutic subgroups with new drugs grow significantly faster than average expenditure, but this growths is counterbalanced by subgroups which in the end of their innovation cycle and a huge proportion of generic drugs. Conclusion: The growths of net drug expenditure in the German SHI does not threaten the sustainability of financing health expenditure based on comprehensive policy measures and innovation cycle effects. Generics do contribute savings to a larger extent.
urn:nbn:de:bvb:861-opus4-18523
Keywords: 330; German social health insurance; generic drugs; health policies